Phylogenetic relationships between four catfish species (family clariidae) inferred from analysis of cytochrome B mitochondrial DNA gene - Nurziehan, Binti Mohamed (Universiti Malaysia Sarawak, UNIMAS, 2012)
This study examined 405 base pairs of the mitochondrial cytochrome b gene from 13 individuals consist of four species (Clarias batrachus, Clarias intermedius, Clarias leiancanthus and Clarias nieuhofii) from the family Clariidae. The samples were taken from Balai Ringin, Sarawak. Phylogenetic reconstruction was accomplished by Maximum Likelihood, Maximum Parsimony, Neighbour Joining analyses, and Bayesian Analysis methods. Phylogenetic analysis supported the monophyletic status between all the four species of catfish. Overall, the partial sequence of the mitochondrial DNA cytochrome b gene was useful for resolving the phylogenetic relationships among Clariidae family.